Early TV Viewing and Childhood Attention Deficits - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
The National Longitudinal Survey of Youth, a nationally representative longitudinal data set, was used at the University of Washington, Seattle, to test the hypothesis that early television exposure (at ages 1 and 3) is associated with attentional problems (AP) at age 7.